2012
DOI: 10.1111/j.1532-5415.2011.03854.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment with Osteoporosis Medications After Recent Fragility Fractures in a Multinational Cohort of Postmenopausal Women

Abstract: OBJECTIVES To determine the proportion of untreated women who reported receiving treatment after incident fracture and to identify factors that predict treatment across an international spectrum of individuals. DESIGN Prospective observational study. Self-administered questionnaires were mailed at baseline and 1 year. SETTING Multinational cohort of noninstitutionalized women recruited from 723 primary physician practices in 10 countries. PARTICIPANTS Sixty thousand three hundred ninety-three postmenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…A recent study of men revealed treatment rates of 7% to 9% following any fracture and 7% following hip fracture 32 , with older studies showing lower rates 33 . Consistent with our findings, previous investigators observed higher treatment rates among women than among men 30,33 and among those with a vertebral fracture than among those with another type of fracture 31,33 . Similar to our study, systematic reviews of adherence to bisphosphonate therapy have shown that the average twelve-month medication possession ratio is typically 60% to 70%, and ‡43% of patients achieve a ''high'' twelve-month adherence of >80% 10,11,13 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A recent study of men revealed treatment rates of 7% to 9% following any fracture and 7% following hip fracture 32 , with older studies showing lower rates 33 . Consistent with our findings, previous investigators observed higher treatment rates among women than among men 30,33 and among those with a vertebral fracture than among those with another type of fracture 31,33 . Similar to our study, systematic reviews of adherence to bisphosphonate therapy have shown that the average twelve-month medication possession ratio is typically 60% to 70%, and ‡43% of patients achieve a ''high'' twelve-month adherence of >80% 10,11,13 .…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, U.S. studies using data from the 1990s and early 2000s showed that <5% of female patients who sustained a fracture underwent DXA testing and 20% to 45% started or initiated osteoporosis treatment following the fracture [27][28][29][30] . A recent multinational study demonstrated that 17% of 1075 postmenopausal women initiated treatment following an incident fracture 31 . A recent study of men revealed treatment rates of 7% to 9% following any fracture and 7% following hip fracture 32 , with older studies showing lower rates 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed that the percentage of those with a baseline fracture who received OP treatment (24.1%) was lower than that of the entire cohort (28.6%). The finding that those whose OP was identified from diagnosis codes (instead of a fracture) had higher levels of OP treatment parallels results from a previous study that observed that the presence of an OP diagnosis was associated with a greater likelihood of receiving OP pharmacotherapy 9 . Logistic regression analysis revealed that, in the overall cohort, prior use of OP medications was the strongest predictor of OP treatment which is consistent with a previous study of Medicare patients that observed that patients with prior OP treatment had over a nine-fold increase in the odds of appropriate OP management (pharmacological treatment or diagnostic testing) following a fracture, versus those without prior OP treatment 27 .…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have demonstrated that non-treatment of osteoporosis is common [8][9][10][11][12][13][14][15][16][17][18][19][20] , whether assessed after clinical or self-reported OP diagnosis 10,20 , before OP-related fractures 8,11,16 , or after fractures 9,[11][12][13][14][15][16][17][18][19] . Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation